Ethics in Adult Orthodontics (Medico Legal Update, 2020)
Ethics is the understanding and the ability to differentiate right from wrong in human behavior. Dental ethicsdenotes moral duties and obligations of a dental practitioner towards their patients, fellow colleagues, andthe society at large. An ethical practice among dentists ensure good patient care in concurrence with theirtreatment needs. Ethical principles and codes introduced by regulatory bodies benefit the patient, avoidharm, and respect patient’s preferences. Ethical dilemmas are faced by orthodontists during orthodonticinterventions, even though important human values may be at stake during the course of treatment. Thecode of ethics in dentistry warrants an orthodontist to act in the best interest of their patients regardless oftheir financial status, even putting themselves at jeopardy if need be. This article thus focuses on the moralsand ethics that should be abided by an orthodontist in order to deliver the best possible care to their patients.